IMPLEMENTASI PENGENDALIAN MANAJEMEN BERBASIS FILOSOFI YIN YANG UNTUK MENGATASI MASALAH PADA CV YOBEL JAYA - Fransiska Dwitari; Sujoko Efferin; Aris Surya Putra (Perpustakaan Universitas Surabaya, 2018)
The industrial revolution has changed the pattern of development of the world economy gradually. Western management philosophies and perspectives are thought to dominate around the world. While the eastern philosophy that has existed for about 2,500 years such as Confucianism, Taoism and Buddhism is only given a very limited attention and appreciation. However, over time business practices in China have proved that the perfect combination of Western management ideas and traditional Chinese culture has made the Chinese business model so dynamic that it is becoming widely used in the world. One of the core concepts of Chinese Taoist philosophy that is most familiar with western thinking is Yin Yang. This philosophy provides an insight into a statement that seems to contradict popular opinion. However, in the midst of complex needs and tight competition to meet today's business needs, Yin-Yang's principle of balance is an important guide to solving existing problems. The research method used is applied research because this research is useful to solve the problem problems according to the selected research object. The purpose of this study is exploratory research where this research will explain the implementation of control management based on Yin Yang philosophy in solving business problems on the object of research.